Burned‐Out Testis Tumors in Asymptomatic Infertile Men: Multiparametric Sonography and MRI Findings. (3rd December 2016) - Rocher, Laurence; Glas, Ludivine; Bellin, Marie France; Ferlicot, Sophie; Izard, Vincent; Benoit, Gerard; Albiges, Laurence; Fizazi, Karim; Correas, Jean‐Michel
Abstract : Multiparametric testicular ultrasound and magnetic resonance imaging (MRI) findings were analyzed in a series of 10 infertile asymptomatic men presenting with pathologically confirmed burned‐out testicular tumors. Color/power Doppler ultrasound (CDUS), shear wave elastography (SWE), contrast‐enhanced ultrasonography (CEUS), and MRI were performed on 10, 5, 6, and 7 patients, respectively. All lesions appeared as a hypoechoic and hypovascular nodular area at CDUS, SWE, CEUS CDUS, and CEUS (if performed). Shear wave elastography showed a stiffer nodular area compared with the surrounding/contralateral tissues (13 versus 2 kPa); MRI revealed a well‐delineated nodular area in hypointense signal on T2, a high apparent diffusion coefficient value, and a lack of enhancement.